2015
DOI: 10.1136/gutjnl-2014-308578
|View full text |Cite
|
Sign up to set email alerts
|

Population-based assessment of the outcomes in patients with postcolonoscopy colorectal cancers

Abstract: Compared with CRC detected by colonoscopy, PCCRCs are associated with a higher risk of emergent presentation, a lower likelihood of surgical resection and most notably, significantly worse oncological outcomes. However, they have better outcomes than patients with no recent colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 26 publications
2
20
1
Order By: Relevance
“…Significantly more in situ tumors were found in the PCCRC group. This in contrast to other studies 18 , where a higher likelihood of stage IV disease was found.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Significantly more in situ tumors were found in the PCCRC group. This in contrast to other studies 18 , where a higher likelihood of stage IV disease was found.…”
Section: Discussioncontrasting
confidence: 99%
“…We demonstrated that conditional survival for PCCRC was worse than for CRC. This outcome was also reported by Govindarajan et al 18 who found that PCCRCs were associated with a significantly worse oncological outcome. Most other studies, however, showed no difference in survival between individuals with PCCRC and controls 6 13 22 23 .…”
Section: Discussionsupporting
confidence: 86%
“…Similar to PCCRC, tumours developing through the MMR pathway are more likely to be found in proximal locations and in older patients. These cancers may grow more quickly than tumours from the classic chromosomal instability pathway, without the slow progression from adenoma to carcinoma [39][40][41] has therefore been partly attributed to lead time bias [45,46]; once adjusted for, the survival difference between patients with PCCRC and detected cancers attenuates [47] This study is population-based and thus results reflect the general population of patients diagnosed with CRC after undergoing colonoscopy in Ontario. Further, we have included only patients with confirmed PCCRC.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, several studies have demonstrated similar survival among patients with PCCRC and detected cancers. In a Danish population‐based study of 982 patients with PCCRC and 35 704 patients who did not undergo colonoscopy prior to the diagnostic procedure, the adjusted 2–5‐year mortality rate ratio was 1.0 (95% CI 0.88–1.20) [14] Similarly, in a Korean population‐based study that included 6130 patients with PCCRC and 72 030 patients with detected cancers, both groups demonstrated similar unadjusted 5‐year survival (78.0% vs. 76.8%, respectively) [18] Unadjusted 5‐year survival was also similar in a single‐institution study of 51 patients with PCCRC matched to 112 patients with detected cancers (44% vs. 41%, respectively) [29] Although one study reported patients with PCCRC to have better overall survival than those with detected cancers (HR 0.63; 95% CI 0.49–0.81) [27] a subsequent study from the same group that matched patients by age, sex and hospital site did not find differences in survival between groups [42] Poorer survival may be expected given the aetiology of PCCRC; however, multiple studies report these cancers actually present at earlier stages than detected cancers [6,19,27] The poorer survival seen in some studies has therefore been partly attributed to lead time bias [45,46]; once adjusted for, the survival difference between patients with PCCRC and detected cancers attenuates [47]…”
Section: Discussionmentioning
confidence: 99%
“…28 However, this finding is not universal; in a population-based study of PCCRC from Ontario, Canada they reported that PCCRC had a higher likelihood of stage IV disease, worse overall survival, and emergency presentation compared with cancer detected at colonoscopy. 29 Studies of CRC have suggested a survival benefit for those with MSI tumors, 30,31 whereas conflicting reports exist on the effect of CIMP status on patient survival. PCCRC studies from Minnesota also did not find any survival benefits associated with molecular markers CIMP or MSI and actually reported a survival disadvantage in those patients with MSI tumors.…”
Section: Discussionmentioning
confidence: 99%